Osteophytes in the osteoarthritic hand: their incidence, size, distribution, and progression. Issue 9 (September 1991) - Buckland-Wright, J C; Macfarlane, D G; Lynch, J A
Abstract : Quantitative microfocal radiographic assessment of osteophytes in osteoarthritic hands showed that their number and area were greatest at joint margins, in the dominant hand, in the second and third compared with fourth and fifth phalanges, in the third phalanx, and in the second distal interphalangeal joint respectively. These sites correspond with those for the largest forces exerted in the hand: the dominant side, the finger tripod used in the precision grip, power grip, and pulp-pinch respectively. The greater osteophytosis on the trapezium of the nondominant first carpometacarpal joint was probably related to forces exerted during power grip. Osteophytes increased significantly in number and area during the 18 month study period.